OPPORTUNITIES OF MODERN UNDERSTANDINGS ON HUMAN CAPITAL - Stoyanov, Evgeniy (Journal of Economic Development, Environment and People, 2016)
The study is focused on the key factor in the structure of any organization – the human capital. The objective is to present the thesis of the author that it is possible to optimize the process of formation of human capital through consolidated administration of certain management and control concepts. The tasks are connected with accumulation of evidence that the concept of the audit of human resources can be and should be developed.